Distribution of ABO and Rh blood Groups Among Tribal Population of Sylhet, Bangladesh - Begum, D; Amin, MR; Khatun, F; Ahmed, SS; Sinha, SK; Rahman, MA (Journal of Dhaka Medical College, 2011)
Context: Distribution of blood groups varies among ethnic groups throughout the world. Blood groups of tribals should be determined as they are ethnically different from the main population of Bangladesh. Materials and Methods: To observe the distribution pattern of ABO and Rh blood groups and to compare the groups among Manipuris (1434) and Khasias (204), this descriptive crosssectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka, from July 2006 to June 2007. Manipuris were divided in Bishnupriya (658), Meitei (460) and Meitei-Pangan (316) according to their ethnic origin. Data were collected from Manipuri (12) and Khasia (2) localities selected by systematic random sampling. ABO and Rh blood groups of participants were determined by the antigen antibody agglutination test of slide method. Data from groups were compared by chi-square test with 95% confidence limit. Results: There are significant variations in the distribution of ABO (p<0.001) and Rh (p<0.001) blood groups among all study groups. Blood group A was more frequent among Meiteis (40%) and Meitei-Pangans (42.41%) whereas blood group O was more frequent in Bishnupriyas (47.72%) and Khasias (35.29%). In all tribal communities, AB blood group was least frequent. Rh positive participants (97.43%) were more than Rh negative (2.57%). In Khasias, no Rh negative group was found. Rh negativity was more in Bishnupriyas (4.9%) which was significantly higher than Meiteis (0.87%) and Meitei-Pangans. (1.94%) (X2=16.7; p<0.001). Conclusion: Distribution of ABO blood groups varies among the Manipuris and Khasias. Significant variation is also found in three groups of Manipuris and the distribution corresponds with the pattern of their ancestors. Key words: ABO blood group; Rh blood group; tribal population; Sylhet. DOI: http://dx.doi.org/10.3329/jdmc.v20i1.8581 J Dhaka Med Coll. 2011; 20(1) :44-50